Loco-regional treatment with temozolomide-loaded thermogels prevents glioblastoma recurrences in orthotopic human xenograft models - Lisa Gherardini; Veronica Vetri Buratti; Mirko Maturi; Giovanni Inzalaco; Erica Locatelli; Letizia Sambri; Sara Gargiulo; Virginia Barone; Denise Bonente; Eugenio Bertelli; Silvia Tortorella; Lorenzo Franci; et al. (2023)
Glioblastoma multiforme (GBM) is the most aggressive primary tumor of the central nervous system and the diagnosis is often dismal. GBM pharmacological treatment is strongly limited by its intracranial location beyond the blood-brain barrier (BBB). While Temozolomide (TMZ) exhibits the best clinical performance, still less than 20% crosses the BBB, therefore requiring administration of very high doses with resulting unnecessary systemic side effects. Here, we aimed at designing new negative temperature-responsive gel formulations able to locally release TMZ beyond the BBB. The biocompatibility of a chitosan-β-glycerophosphate-based thermogel (THG)-containing mesoporous SiO2 nanoparticles (THG@SiO2) or polycaprolactone microparticles (THG@PCL) was ascertained in vitro and in vivo by cell counting and histological examination. Next, we loaded TMZ into such matrices (THG@SiO2-TMZ and THG@PCL-TMZ) and tested their therapeutic potential both in vitro and in vivo, in a glioblastoma resection and recurrence mouse model based on orthotopic growth of human cancer cells. The two newly designed anticancer formulations, consisting in TMZ-silica (SiO2@TMZ) dispersed in the thermogel matrix (THG@SiO2-TMZ) and TMZ, spray-dried on PLC and incorporated into the thermogel (THG@PCL-TMZ), induced cell death in vitro. When applied intracranially to a resected U87-MG-Red-FLuc human GBM model, THG@SiO2-TMZ and THG@PCL-TMZ caused a significant reduction in the growth of tumor recurrences, when compared to untreated controls. THG@SiO2-TMZ and THG@PCL-TMZ are therefore new promising gel-based local therapy candidates for the treatment of GBM.